Geochemical classification and secondary alteration of crude oil in the southern thrust belt of Junggar Basin - Qin, Zhijun; Qi, Hongyan; Liang, Zeliang; Ma, Wanyun; Wang, Ruiju; Wu, Wei’an (Frontiers in Earth Science, 2023)
In this study, 18 oil samples collected from four representing oil-bearing secondary tectonic units in the southern thrust belt of Junggar Basin were analyzed. Based on the characteristics of light hydrocarbon compounds, adamantanes, steroidal/terpene biomarkers and stable carbon isotopic composition of the bulk oil, the genetic types and the secondary alteration of oil were discussed. The results show that the oil in the study area can be divided into five categories. Type I is characterized by 13C-depleted carbon isotope, low ratio of pristane to phytane, high gammacerane and low rearranged sterane, while Type II shows the opposite characteristics. Type III is very similar to Type II oil, but shows a more 13C-depleted bulk carbon isotopic composition and a wider carbon numbers of tricyclic terpene. Type IV and V oils are similar to Type I, except for a relatively lower content of gammacerane. Type IV oils also have high ααα 20R regular steranes, 13C-enriched bulk oil carbon isotopes and higher ratio of pristane to phytane. In contrast, the relative content of C27 regular steranes of Type V oils is much lower than that of Type I. The oil in the study area have not suffered from biodegradation. The maturity information indicated by regular biomarkers (i.e., steroid, terpane, and thephenanthrene) and adamantine differs significantly with the later showing a strong cracking characteristics. This reflects the charging and mixing of oils formed at different evolution stages. All the other types of oils are in the normal oil-generating-window without suffering strong cracking. The oil in the study area is generally subjected to evaporative fractionation, but there are obvious differences in the degree of alteration between different oil-bearing structures and different reservoirs of the same structure. This study is of great significance for understanding the origin and accumulation process of oil and gas in complex structural zone.